Correlation of Self-Reported Questionnaire (KOOS) with Some Objective Measures in Primary OA Knee Patients. (16th January 2014) - Sivachidambaram, Kulandaivelan; Ateef, Mahamed; Tahseen, Shaziya
Abstract : Purpose . Objective of the present study was to see the correlation of subjectively measured KOOS questionnaire with objectively measured 6-minute walk test (6-MWT), age, height, weight, and BMI. Participants . 251 subjects with OA knee based on American College of Rheumatology criteria. Methods . After passing inclusion and exclusion criteria, the following parameters were recorded: age, height, weight, and BMI. Then subjects were asked to fill KOOS questionnaire; then all subjects were asked to do self-paced walk for 6 minutes. Analysis . Spearman rank test was done to see the correlation. Significant level was set atP < 0.05 . Results . 6-MWT had a weak correlation with KOOS-ADL (rho 0.461) and strong correlation with KOOS-symptom, KOOS-pain, and KOOS-sports and very strong correlation with KOOS-QOL. BMI had a strong correlation with KOOS-pain, KOOS-symptom, KOOS-ADL, and KOOS-sports and very strong correlation with KOOS-QOL. Weight had a weak correlation with KOOS-symptom, KOOS-ADL, and KOOS-sports and strong correlation with KOOS-pain and KOOS-QOL. All the above values were significant withP < 0.001 . Conclusion . KOOS is strongly positively correlated with 6-MWT and negatively correlated with BMI. Its correlation strength has decreased with weight.